Measurement of exclusive ϒ photoproduction from protons in pPb collisions at √sNN = 5.02 TeV - Sirunyan, A. M. (2019)
The exclusive photoproduction of ϒ(nS) meson states from protons, γ p → ϒ(nS) p (with n = 1, 2, 3), is studied in ultraperipheral pPb collisions at a centre-of-mass energy per nucleon pair of √ sNN = 5.02 TeV. The measurement is performed using the ϒ(nS) → μ + μ − decay mode, with data collected by the CMS experiment corresponding to an integrated luminosity of 32.6 nb−1. Differential cross sections as functions of the ϒ(nS) transverse momentum squared p2T , and rapidity y, are presented. The ϒ(1S) photoproduction cross section is extracted in the rapidity range |y| < 2.2, which corresponds to photon–proton centre-ofmass energies in the range 91 < Wγ p < 826 GeV. The data are compared to theoretical predictions based on perturbative quantum chromodynamics and to previous measurements.